Consumer resilience in war conditions in Ukraine: Travel market case - Iuliia Kostynets; Valeriia Kostynets (Contemporary Economics, 2023)
The article is devoted to the study and modeling of the behavior of Ukrainian consumers in the tourist services market in the context of the Russian military invasion of Ukraine. The authors conducted a study of current global market trends in the aspect of the functioning of the industry in the conditions of war in Ukraine. The authors identified prospects for the restoration and development of the tourist services market in the context of further stabilization and improvement of the situation in Ukraine. The article analyzes the potential and realized consumer demand in the market of tourist services in Ukraine. The authors analyzed the results of a survey of tourism business professionals, as well as consumer requests, in order to establish changes in consumer preferences over the past 5 years. Based on the use of the SARIMA model, the authors calculated the forecast values of the frequency of consumer requests for specific tourist destinations 12 steps ahead. The results obtained in the course of the study confirmed the hypothesis of stable consumption of tourist services by Ukrainian consumers.
Keywords: C59; D12; M31; Z32; Z33; 330; consumer resilience; continued pent-up demand; travel market; the Russian invasion of Ukraine